Effects of substrate medium and container type in hydroponically grown strawberries - Tzortzakis, Nikos G. (My University, 2014)
Strawberry (Fragaria x ananassa Duch.) plants were grown hydroponically in cocosoil (Coc), pumice (Pum) and Coc:Pum (50:50) mixtures in multi-channels or pots. In multi-channels, the number of leaves and runners (stolons) doubled in plants grown in Coc comparing with the control treatment (Pum), while in pots; strawberry plants produce increased number of runners in Coc. Flower number increased (up to 55%) in plants grown in Pum in multi-channels while no differences observed for the number of flowers in plants grown in pots. Leaf stomatal conductance, photosynthetic rate and internal concentration of CO2 differentiated according to the plant vegetative or reproductive stage and/or substrate medium, with higher values marked in Coc-based substrates. Leaf and stem fresh weight as well as leaf area was increased (up to 72%, 82% and 96% respectively) in case of Coc comparing with the Pum. Fruit number increased but fruit fresh weight decreased in plants grown in Coc, comparing with plants grown in Pum, resulting in similar plant yields for the examined substrate medium. However, considering plant density, the double number of plants grown in multi-channels comparing with pots, thus the total yield was greater. Substrates and/or container type had little effect in fruit quality parameters. The present findings highlights the putative use of organic medium i.e., cocosoil as substrate medium in strawberry culture, while the container type may affect the crop yield.
Keywords: Marketability; Organic materials; Plant growth; Soilless culture; Yield